Striatal α5 nicotinic receptor subunit regulates dopamine transmission in dorsal striatum. - Exley, R; McIntosh, J; Marks, M; Maskos, U; Cragg, S (2012)
Polymorphisms in the gene for the α5 nicotinic acetylcholine receptor (nAChR) subunit are associated with vulnerability to nicotine addiction. However, the underlying normal functions of α5-containing nAChRs in the brain are poorly understood. Striatal dopamine (DA) transmission is critical to the acquisition and maintenance of drug addiction and is modulated strongly by nicotine acting at heteromeric β2-containing (β2*) nAChRs. We explored whether α5 subunits, as well as α4, α6, and β3 subunits, participate in the powerful regulation of DA release probability by β2* nAChRs in nucleus accumbens (NAc) core and in dorsal striatum [caudatoputamen (CPu)]. We detected evoked dopamine release using fast-scan cyclic voltammetry at carbon-fiber microelectrodes in striatal slices from mice with deletions of α4, α5, α6, or β3 subunits. We show that the nAChR subtypes that dominantly regulate dopamine transmission depend critically upon α5 subunits in the dorsal CPu in α4α5(non-α6)β2-nAChRs but not in NAc core, where α4α6β2β3-nAChRs are required. These data reveal the distinct populations of nAChRs that govern DA transmission in NAc core versus dorsal CPu. Furthermore, they indicate that α5 subunits are critical to the regulation of DA transmission by α4β2* nAChRs in regions of striatum associated with habitual and instrumental responses (dorsal CPu) rather than pavlovian associations (NAc).